The Palgrave Handbook on the Pedagogy of International Relations Theory
LI, 894 p. 17 illus., 14 illus. in color.
Keywords: The Palgrave Handbook on the Pedagogy of International Relations Theory is a collection that explores how best to teach the systems of thought that organize the study of international relations and global politics. All chapters document and advance intradisciplinary conversations about the challenge of helping students understand the nuances of IR theory. Authors document strategies they have successfully applied to that challenge in a variety of contexts and encourage readers to creatively adapt to the challenges of their own pedagogical contexts. The handbook is organized around four themes – teaching theory for particular audiences and classroom contexts, tips for teaching specific theories, an exploration of pedagogical approaches to teaching theory, and pedagogical considerations specific to courses in geographic regions. Jamie Frueh is Associate Provost and W. Harold Row Professor of International Studies at Bridgewater College in Virginia, USA. Jacqui Ala is Associate Professor and the Head of International Relations (IR) at the University of the Witwatersrand in Johannesburg, South Africa. Michael Murphy is a Buchanan Postdoctoral Fellow in the Department of Political Studies, Queens University, Kingston, Ontario, Canada. Paul F. Diehl is Henning Larsen Professor Emeritus of Political Science at the University of Illinois at Urbana-Champaign and Ashbel Smith Professor Emeritus of Political Science at the University of Texas-Dallas. “This book is the ultimate guide to the state-of-the-art of the pedagogy of IR. Comprehensive in scope and authored by a diverse group of scholars, this will become an indispensable resource for all teachers and students committed to making the field of IR more inclusive and vibrant.” Amitav Acharya, UNESCO Chair in Transnational Challenges and Governance, American University “A timely and much-needed intervention. Pedagogy is going to become a centerpiece of pluralizing the discipline of international relations. Those teaching, learning, or doing international relations across the globe will find this volume to be an excellent resource and of lasting value.” Navnita Chadha Behera, Professor, Department of Political Science, University of Delhi.